The Importance of Transition from Micro to Nano Clay Size in Improving the Engineering Properties of Sandy Soils (Poorly Graded Sand) - J. Sufiyan; A. Uromeihy; M.R. Nikudel (Global Journal of Earth Science and Engineering, 2015)
Nano-clays are a broad class of naturally occurring inorganic minerals in the form of plate-like alumina-silicate layers with thickness between 1nano-meter to 10micro-meters. Due to the very small sizes of nanoparticle, they provide a large specific surface area which make them to absorb water and fill the voids within the soil particles. The aim of this paper is to investigate the use of nano-clays for modifying the engineering properties of granular soils. This type of soil covers large parts of the land surface and cause many problems for the development of urban areas, infrastructure projects and instability of slopes along the railways and road networks. The mineral composition of the granular soil mainly consists of quartz grains and the soil types are classified as poorly- to well-grade materials. In order to evaluate the effect of micro and nano clay on modification of geotechnical properties of the sand, different percentage of 0.5%, 1%, 2% and 4% of micro-clay and percentage 0.5%, 1%, 2%, 4%, 6%, 8%, 10%, 12% and 14% nano-clay. In order to determine the value of its peak were done. Then mixed with the sand and a number of tests such as compaction test, direct shear test are conducted on the samples. The result shows that maximum dry unit weight and maximum optimum moisture content were obtained when 10% nano-clay mixed with the sand. It was also was noted that the increment of nano-clay and micro-clay causes gradual increases and gradual decreases of the shear strength of the sample, respectively.